Multiplicity of disc-bearing stars in Upper Scorpius and Upper Centaurus-Lupus. Issue 4 (3rd August 2018) - Kuruwita, Rajika L; Ireland, Michael; Rizzuto, Aaron; Bento, Joao; Federrath, Christoph
ABSTRACT: We present observations of disc-bearing stars in Upper Scorpius (US) and Upper Centaurus-Lupus (UCL) with moderate resolution spectroscopy in order to determine the influence of multiplicity on disc persistence after ${\sim }5\hbox{--}20\, Myr$ . Discs were identified using infrared (IR) excess from the Wide-field Infrared Survey Explorer (WISE) survey. Our survey consists of 55 US members and 28 UCL members, using spatial and kinematic information to assign a probability of membership. Spectra are gathered from the ANU 2.3 m telescope using the Wide Field Spectrograph (WiFeS) to detect radial velocity variations that indicate the presence of a companion. We identify two double-lined spectroscopic binaries, both of which have strong IR excess. We find the binary fraction of disc-bearing stars in US and UCL for periods up to 20 yr to be $0.06^{+0.07}_{-0.02}$ and $0.13^{+0.06}_{-0.03}$, respectively. Based on the multiplicity of field stars, we obtain an expected binary fraction of ${\sim }0.12^{+0.02}_{-0.01}$ . The determined binary fractions for disc-bearing stars do not vary significantly from the field, suggesting that overall lifetime of discs may not differ between single and binary star systems.